PEMBANGUNAN GAMPONG DENGAN SEMANGAT GOTONG ROYONG MELALUI MUSYAWARAH DAN KETERBUKAAN DI KABUPATEN ACEH BARAT - Teuku Ahmad Yani (Universitas Teuku Umar, 2017)
Development activities independently by society Gampong is not a new thing in the country of Indonesia, it's just that more development activities based on the limitations of the use of the resources of the gampong both in terms of both financial resources his human. Therefore, mutual is the main way for people to development Gampong. In tune with the enacted law on Gampong, then mutual culture be reduced, where as the presence of State money in Gampong development in to additional energy from the spirit of Indonesia. The results showed that implementing the construction of Gampong, there are still many obstacles, but the existence of the deliberations conducted by Lord Peuet has been able to solve the problem, because the deliberations deliberations remained the leading solutions in gampong daam resolves the problem. In order for the deliberation can be meaningful so any executing development must be open to problems occurred, likewise should willingly and respect any result of deliberation a mutually agreed. Keywords: Gampong, Keuchik, Finance